American individualism rises and falls with the economy Cross-temporal evidence that individualism declines when the economy falters. [article]. - Bianchi, Emily C.
Past work has shown that economic growth often engenders greater individualism. Yet much of this work charts changes in wealth and individualism over long periods of time, making it unclear whether rising individualism is primarily driven by wealth or by the social and generational changes that often accompany large-scale economic transformations. This article explores whether individualism is sensitive to more transient macroeconomic fluctuations, even in the absence of transformative social changes or generational turnover. Six studies found that individualism swelled during prosperous times and fell during recessionary times. In good economic times, Americans were more likely to give newborns uncommon names (Study 1), champion autonomy in children (Study 2), aspire to look different from others (Study 3), and favor music with self-focused language (Study 4). Conversely, when the economy was floundering, Americans were more likely to socialize children to attend to the needs of others (Study 2) and favor music with other-oriented language (Study 4). Subsequent studies found that recessions engendered uncertainty (Study 5) which in turn tempered individualism and fostered interdependence (Study 6).-- (from the authors)